The warrior's character [ leadership wisdom from West Point's cadet prayer - Snider, Don M. (McGraw-Hill, 2013)
As one of America's most honored institutions, West Point has produced some of the greatest leaders in the history of the nation - and the world. This title looks into West Point's development of leaders of character through the Army's seven primary, timeless values: loyalty; duty; respect; service; honor; integrity; and courage